DOI: 10.18297/etd/1381
|View full text |Cite
|
Sign up to set email alerts
|

School-based decision making (SBDM) councils and their efficacy and productivity as perceived by council members.

Abstract: husband, Thomas, and son, Michael, for all of the sacrifices they made so that this is even possible.I would also like to dedicate this to my parents, Sharon and Rod Shrout, who instilled in me a love and appreciation for education and life-long learning. The results of the study showed that, in general, council members had a positive perception of the productivity and efficacy of the councils. There were no differences between the perceptions of parents and principals, nor between principals and teachers/staf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The practice of SDM was expected to result in improved student learning, more effective school management, and an empowered teacher workforce (McNeill and McNeill, 1994). Similar to SDM was site-based decision making as mandated in Texas in 1990 (Noel, Slate, Brown, and Tejeda-Delgado, 2008), school-based decision making in Kentucky legislation in 1990 (Stenton, 2010), and school community-based management in Hawaii (Reinventing Education Act of 2004).…”
Section: Shared Decision-making and School Community Councilsmentioning
confidence: 99%
See 1 more Smart Citation
“…The practice of SDM was expected to result in improved student learning, more effective school management, and an empowered teacher workforce (McNeill and McNeill, 1994). Similar to SDM was site-based decision making as mandated in Texas in 1990 (Noel, Slate, Brown, and Tejeda-Delgado, 2008), school-based decision making in Kentucky legislation in 1990 (Stenton, 2010), and school community-based management in Hawaii (Reinventing Education Act of 2004).…”
Section: Shared Decision-making and School Community Councilsmentioning
confidence: 99%
“…Some schools and principals that implemented SDM experienced conflict with arguably less educational change occurring than non SDM schools (Weiss and Cambone, 1994). In order to be effective, SDM required change-oriented leadership and teacher leadership (Weiss and Cambone, 1994), enabling conditions such as focusing on student achievement and sharing power and problem-solving networking through committees (Talley and Keedy, 2006), training and development, and receiving relevant information (Stenton, 2010). In a qualitative study on site-based decision-making in Texas, Noel et al (2008) found that principals and teachers perceived SBDM differently and both groups may not be prepared well for SBDM without adequate training.…”
Section: Shared Decision-making and School Community Councilsmentioning
confidence: 99%